Peran Orang Tua dalam Mengembangkan Minat Belajar Anak Berkebutuhan Khusus Tunagrahita Selama Pandemi Covid-19 - Astutiyanti Hersi Tandiarrang; Lutma Ranta Allolinggi; Marilyn Lasarus (Jurnal Keguruan dan Ilmu Pendidikan, 2022)
This study aims to find out how the role of parents in educating mentally retarded children during the Covid-19 pandemic is and how they are interested in learning with mentally retarded children during the Covid-19 pandemic. This type of research is a qualitative research with a descriptive design, this research lasts for several days. Data collection procedures in this study were observation, interviews, and documentation. The results of the study show that parents play an important role in the learning of children with special needs for mental retardation during the covid-19 pandemic. This is evidenced when children take online learning, parents prepare facilities that will be used by children during online learning and parents guide during learning. And the learning interest of children with special needs for mental retardation in learning is very high. very enthusiastic in doing the assignments given by the teacher.